2008
DOI: 10.1074/jbc.m805485200
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Collagen Studies Link the Severe Conformational Changes Induced by Osteogenesis Imperfecta Mutations to the Disruption of a Set of Interchain Salt Bridges

Abstract: The clinical severity of Osteogenesis Imperfecta (OI), also known as the brittle bone disease, relates to the extent of conformational changes in the collagen triple helix induced by Gly substitution mutations. The lingering question is why Gly substitutions at different locations of collagen cause different disruptions of the triple helix. Here, we describe markedly different conformational changes of the triple helix induced by two Gly substitution mutations placed only 12 residues apart. The effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 28 publications
(55 reference statements)
0
45
0
Order By: Relevance
“…However, as cited above, a Gly to Ser mutation can lead to a mild, a severe, or a lethal OI case, with no obvious molecular explanation. Other factors suggested to contribute to clinical phenotype include the rigidity of its immediate sequence environment; its location with respect to the C terminus; its proximity to salt bridges; and its presence at an interaction site, such as the binding site for proteoglycans on collagen fibrils (7,9). A recent study of the stability of OI collagens supported the importance of the domain location of the mutation (10), whereas a network analysis of the mutations suggested the importance of a destabilizing tripeptide sequence C-terminal to the mutation site (11).…”
mentioning
confidence: 99%
“…However, as cited above, a Gly to Ser mutation can lead to a mild, a severe, or a lethal OI case, with no obvious molecular explanation. Other factors suggested to contribute to clinical phenotype include the rigidity of its immediate sequence environment; its location with respect to the C terminus; its proximity to salt bridges; and its presence at an interaction site, such as the binding site for proteoglycans on collagen fibrils (7,9). A recent study of the stability of OI collagens supported the importance of the domain location of the mutation (10), whereas a network analysis of the mutations suggested the importance of a destabilizing tripeptide sequence C-terminal to the mutation site (11).…”
mentioning
confidence: 99%
“…46 All crystal structures show hydrogen bonds between the NH of Gly in one chain and the C¼O of the residue at the X position of the neighboring chain. 16,50,51 When the Y position is occupied by an amino acid rather than an imino acid, it is hydrated by water molecules and directed into the solvent, which reduces the helix stability. 19,24 In addition, peptides with the sequence where the X position is occupied by a residue other than Pro show second interchain hydrogen bonds …”
Section: Stability Of Triple Helix Peptidesmentioning
confidence: 99%
“…By using recombinant technology, one can design and amplify a collagen-like triple helix that is monodisperse, easily mineralized with metal ions, and can thus be applied as a rigid biomolecular template for metal/semiconductor nanowire fabrications. 4,16 …”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the difficulty of producing a large repertoire of full-length mutated collagens I in order to undertake a genotype/phenotype analysis, a recombinant trimeric minicollagen I was recently expressed in an Escherichia coli system. Recombinant mini-collagens can be obtained by fusing the sequence encoding a fragment of the pro1(I) chain triplehelix to the sequence encoding the C-terminal domain (called "foldon") of the bacteriophage T4 fibritin, which is capable of trimerization (Xu et al, 2008). Two mutations (G901S and G913S), corresponding to mild and severe types of OI, respectively, were introduced into the recombinant mini-collagen I. Biophysical measurements and protease cleavage analysis revealed that the G913S mutant chain resulted in the formation of an unstable collagen I triple helix by disrupting salt bridges important for maintaining the chains in a triple-helix conformation (Yang et al, 1997;Xu et al, 2008).…”
Section: Lessons From Site-directed Mutagenesis Of Recombinant Collagmentioning
confidence: 99%
“…Recombinant mini-collagens can be obtained by fusing the sequence encoding a fragment of the pro1(I) chain triplehelix to the sequence encoding the C-terminal domain (called "foldon") of the bacteriophage T4 fibritin, which is capable of trimerization (Xu et al, 2008). Two mutations (G901S and G913S), corresponding to mild and severe types of OI, respectively, were introduced into the recombinant mini-collagen I. Biophysical measurements and protease cleavage analysis revealed that the G913S mutant chain resulted in the formation of an unstable collagen I triple helix by disrupting salt bridges important for maintaining the chains in a triple-helix conformation (Yang et al, 1997;Xu et al, 2008). A very recent study utilized a recombinant bacterial collagen to develop a mutagenesis scheme in which a glycine residue within the triple-helix sequence is substituted with arginine or serine.…”
Section: Lessons From Site-directed Mutagenesis Of Recombinant Collagmentioning
confidence: 99%